Método para dimensionamento eficiente de reservatórios de contenção de cheias para a cidade de Curitiba-PR - Souza, Ricardo Cesar Conrado de (2018)
The impacts caused by rainfall in urban areas indicate the need to approach measures for managing urban drainage, in order to avoid losses arising from runoff, such as floods. Brazilian urban drainage is considered outdated, because the concept of channeling is more used than the reservation and infiltration, prioritizing fast flowing instead of controlled disposal of reserved volumes. The city of CuritibaPR has a Municipal Decree Number 176/2007, responsible for the criteria for implementation of flood containment mechanisms. However, the established design guidelines do not guarantee minimum performance for flood detention tanks, since it may vary depending on their base area, water depth and flow regulator’s orifice diameter. In this research is proposed a sizing method, establishing criteria that relate waterproofed areas of the lots to the tank design parameters, ensuring the function of this control measure. Considering that tanks must provide the given waterproofed area return to its condition before urbanization in contributing flows, determine the value of the required peak flow reduction in 70,24%, obtained from the relation between the coefficients of runoff in both waterproofing conditions. From flow propagation simulations with Pulz Method in generic waterproofed areas at constant intervals adopted for the research, graphs of the geometric characteristics of the reservoirs are obtained as a function of the contribution flow that each generic area receives. From the behavioral analysis, sizing equations are proposed for the parameters of volume, base area, water depth and flow regulator’s orifice diameter, relating them to the present waterproofed areas and ensuring the required efficiency. When comparing the results obtained with the provisions of municipal legislation, in addition to the possibility of improving the efficiency of the reservoirs using other sizing parameters, it points to the possibility of reducing the calculated volume of 24,14% in relation to the current calculation.